PADI4 stimulates esophageal squamous cell carcinoma tumor growth and up‐regulates CA9 expression. Issue 1 (21st October 2018) - Liu, Chunyan; Tang, Junyi; Li, Chang; Pu, Guangbo; Yang, Dongxia; Chang, Xiaotian
Abstract : An increasing amount of evidence indicates that peptidylarginine deiminase isoform 4 (PADI4) plays an important role in tumorigenesis. However, the effects of PADI4 on tumor‐bearing mice are unknown, and no studies have investigated this tumorigenic pathway in an animal model. In the present study, ECA109 cells originating from esophageal squamous cell carcinoma (ESCC) were transfected with PADI4‐expressing lentivirus and were injected into BALB/c nude mice. Tumor size and weight were significantly increased in the mouse tumors established with PADI4‐overexpressing ECA109 cells. PCR array analysis revealed increased CA9 expression in ECA109 cells transfected with a PADI4‐expressing plasmid, while decreased CA9 expression levels were detected in cells transfected with anti‐PADI4 siRNA. Furthermore, up‐regulation of CA9 expression was detected in mouse tumors established with PADI4‐overexpressing cells. Immunohistochemistry detected the increased expression and co‐localization of PADI4 and CA9 in ESCC tissues compared with adjacent non‐tumor tissues and normal tissue controls. These results were verified using Western blotting. Cell proliferation significantly increased or decreased in ECA109 and EC9706 (another ESCC‐originating cell line) cells transfected with a PADI4‐expressing plasmid or anti‐PADI4 siRNA, respectively. The above findings suggest that increased PADI4 expression in ESCC stimulates tumor growth and up‐regulates CA9 expression, which is known to promote metastatic properties in tumor cells.